Burden of rabies in India: the need for a reliable reassessment - Maroof, K A (Indian Journal of Community Health, 2013)
Published literature addressing the issue of burden of rabies in India is scarce. Even the estimates of burden of rabies that are available from various studies differ considerably among themselves and as new data pour in, the earlier available figures are becoming further questionable. It has been almost a decade that a nationwide community based study was done to directly assess the burden of rabies in India. The figures reported by this study is still the most quoted one in published literature. Since this nationwide study has been conducted, there may have been considerable changes in the human and canine demographics as well as the other determinants of rabies at the community level. Policy makers find it difficult to move ahead in planning for rabies control, in the absence of any reliable and evidence based data. The time has come to redesign and redevelop a scientifically robust study design and undertake a nationwide survey to find out the burden of rabies in India.